Flow field and interaction of lifted flames in a triple port burner - Kazuhiro YAMAMOTO; Shinya KATO; Naoki HAYASHI; Hiroshi YAMASHITA (Nihon Kikai Gakkai ronbunshu, 2014)
In this study, we experimentally examined a combustion field in a triple port burner. There are four flame configurations, consisting of attached flames, inner attached/outer lifted flames, inner lifted/outer attached flames, and twin lifted flames. Focusing on the transition process of these flames, the flow field was investigated when the external air flow velocity was increased at constant internal air flow and fuel flow velocities. Results show that, except for the attached flame, when the flame is lifted, the axial velocity toward the leading-edge flame gradually decreases downstream, takes its minimum, and then increases very rapidly. This minimum velocity is larger than the so-called laminar burning velocity. It should be noted that, different from a single lifted flame, the inner or outer flame is affected by the other flame located more upstream. For example, the downstream lifted flame faces the flow induced by the upstream lifted flame. Resultantly, a unique behavior of flip-flop between inner and outer flames is observed.